REVITALISASI AMIL ZAKAT DI INDONESIA Telaah atas Model-model Kreatif Distribusi Zakat - Abdillah, Junaidi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
Baznas (the National Alms Agency) will design as thecoordinator and supervisor of zakat collection anddistribution activities in Indonesia, the world‟s largestMuslim country. This role, he said, would help thegovernment integrate the zakat management system inIndonesia which had been organized independently bycountless registered and unregistered zakat collectionorganizations scattered around the country, and ensurethat the zakat funds would also be used to empowerthe poor. According to the new alms law, the public isstill allowed to establish zakat collection agenciesunder Baznas supervision as long as they meet alladministrative requirements, including the possessionof a recommendation from Baznas and technicalability to run their alms collection and distributionprograms.